Strategic Environmental Assessment : Improving Water Resources Governance and Decision Making - Case Studies - Hirji, Rafik (World Bank, Washington, DC, 2014)
The overall goal of this report is to help water resources and environment professionals within the Bank and client countries use strategic environmental assessment (SEA) to effectively implement the principles of integrated water resources management (IWRM). The report contains four elements: (1) a review of SEA support for IWRM; (2) an analysis of 10 case studies and four water policies; (3) an in-depth pilot study of water sector reform in a developing country; and (4) a framework for enhancing the use of SEAs in integrated water resources management. This SEA provides important lessons on the usage of SEA rather than on the technical aspects of conducting them. It illustrates how an environmental instrument can be used to further development and poverty alleviation as well as environmental protection by putting its findings and recommendations in terms that are meaningful to politicians and senior decision makers. This includes use of economic and financial arguments and linkages to national goals such as poverty reduction and millennium development goals (MDGs). It also illustrates the importance of building support among a wider constituency than just the lead agency and working patiently over a number of years to implement reforms. The influence of an SEA can be felt a number of years as opportunities arise to implement components of a reform program. Finally, it clearly illustrates that an SEA need not be costly or time consuming to be influential if it is focused on the core questions, builds a constituency, and presents its findings in a way that is relevant to decision makers.